The Effectiveness of Online Oxford Dictionary in Improving The Students’ Pronunciation of MTs Mu’Allimin NWDI Pancor - Zuhroni, Siti Fatimatuz; Agustina, Yulia; Wati, Laila; Prasetyaningrum, Ari (Journal of Authentic Research, 2025)
This study aimed at investigating the effectiveness of online Oxford dictionary in improving students’ pronunciation of the seventh-grade students of MTs Mu’allimin NWDI Pancor in the academic year 2025-2026. This research used quantitative approach with a pre-experimental design with one group pretest-posttest design. A total of 25 students participated in this study. The data were obtained by giving pre-test – treatment – post-test. The data were analyzed using paired sample T-test through SPSS 22. The mean post-test score (82,40) was higher than the mean pre-test (56,00). The result pf the Paired sample T test indicated that there was a significant difference between pre-test and post-test, (2-tailed) was 0,00 less than 0,05 (0,00<0,05). Base on the finding, it can be concluded that the use of Online Oxford Dictionary has a significant effect in improving students’ pronunciation at the seventh grade of MTs Mu’allimin NWDI Pancor